POLA PENGGUNAAN TERAPI HIPERBARIK DI RSUP PROF. DR. R. D. KANDOU MANADO PERIODE TAHUN 2013- 2016 - Tulong, Marcella; Hatibie, Mendy; Oley, Maximillian Ch. (e-CliniC, 2016)
Abstract: Besides decompression sickness, hyperbaric oxygen therapy can be used as a therapeutic modality of several diseases inter alia wound healing in gangrene, compromised grafts and flaps, crush injuries, thermal burns, and intracranial abscess. This study was aimed to obtain the usage of hyperbaric oxygen therapy in healing process as indicated. This was a descriptive retrospective study using data of patients who had hyperbaric oxygen therapy performed on them at Prof. Dr. R. D. Kandou Hospital from 2013 to 2016. The results showed that there were 128 patients that had hyperbaric oxygen therapy performed on them,consisted of decompression sickness in 60 patients (46.87%), thermal burn in 29 patients (22.65%), diabetic ulcer in 19 patients (14.84%), followed by crush injury, skin graft, and pre-post amputation in 6 patients each (4.68%), and gangrene in 2 patients (1.56%). Conclusion: The usage of hyperbaric oxygen therapy for decompression was 46.87% and for wound healing was 50.13%.Keywords: hyperbaric oxygen therapy, wound healing Abstrak: Terapi oksigen hiperbarik (TOHB) merupakan salah satu modalitas terapi tambahan yang bisa digunakan sebagai modalitas terapi dari beberapa penyakit selain decompression sickness yaitu penyembuhan luka seperti pada gangrene, compromised grafts and flaps, crush injuries, thermal burns, dan intracranial abscess. Penelitian ini bertujuan untuk mengetahui seberapa banyak penggunaan terapi oksigen hiperbarik sebagai salah satu modalitas terapi pada proses penyembuhan penyakit yang termasuk dalam indikasi. Jenis penelitian ialah deskriptif retrospektif menggunakan data pasien yang melakukan TOHB di RSUP.Prof. Dr. R. D. Kandou periode tahun 2013-2016. Hasil penelitian mendapatkan 128 pasien yang menggunakan TOHB sebagai berikut: decompression sickness sebanyak 60 pasien (46,87 %), luka bakar sebanyak 29 pasien (22,65%), ulkus diabetik sebanyak 19 pasien (14,84%), diikuti crush injury, skin graft dan pre-post amputation masing-masing sebanyak 6 pasien (4,68%), dan gangren 2 pasien (1,56%). Simpulan: Penggunaan TOHB untuk dekompresi sebanyak 46,87% dan untuk penyembuhan luka sebanyak 50,13%. Kata kunci: TOHB, decompression sickness, penyembuhan luka